Introducing anthropology of religion - Eller, Jack David
"This clear and engaging guide introduces students to key areas of the field and shows how to apply an anthropological approach to the study of religion in the contemporary world. Written by an experienced teacher, it covers major traditional topics including definitions, theories and beliefs as well as symbols, myth and ritual. The book also explores important but often overlooked issues such as morality, violence, fundamentalism, secularization, and new religious movements. The chapters all contain lively case studies of religions practiced around the world. The second edition of Introducing Anthropology of Religion contains updated theoretical discussion plus fresh ethnographic examples throughout. In addition to a brand new chapter on vernacular religion, Eller provides a significantly revised chapter on the emerging anthropologies of Christianity and Islam. The book features more material on contemporary societies as well as new coverage of topics such as pilgrimage and paganism. Images, a glossary and questions for discussion are now included and additional resources are provided via a companion website"--